1998
DOI: 10.3892/ijmm_00000124
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in CD44 isoforms and HAS expression in human articular chondrocytes during the de- and re-differentiation processes

Abstract: Abstract. The purpose of this study was to investigate the expression of different CD44 and hyaluronan synthase isoforms in cartilage, their alterations during the chondrocyte dedifferentiation process in monolayer culture and during the redifferentiation process on 3D scaffolds. Chondrocytes isolated from human articular cartilage were cultured as a monolayer for up to 36 days and were seeded on two different 3D scaffolds (HYAFF ® 11 and Bio-Gide ® ). Expression levels of CD44s, CD44-lt, CD44-st, HAS1, HAS2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…Although there are several reports that have shown the expression pattern or functions of HAS isoforms in cell lines, synovial cells or chondrocytes [3,6,1922], there seems no consensus as to how isoform usage affects the synthesis or function of HA in human joints. The present study demonstrates that all three HAS isoforms are expressed in nearly equal copy numbers by the cells of intact OA cartilage and primary chondrocyte cultures with a slight preponderance of HAS1 in the native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several reports that have shown the expression pattern or functions of HAS isoforms in cell lines, synovial cells or chondrocytes [3,6,1922], there seems no consensus as to how isoform usage affects the synthesis or function of HA in human joints. The present study demonstrates that all three HAS isoforms are expressed in nearly equal copy numbers by the cells of intact OA cartilage and primary chondrocyte cultures with a slight preponderance of HAS1 in the native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed upregulation of certain CD44 isoforms during dedifferentiation of chondrocytes in 2D culture [51], suggesting even better binding properties in their dedifferentiated stage. Chondrocytes seeded onto the hyaluronan web for graft generation are also dedifferentiated because they are kept in 2D conditions before 3D cultivation.…”
Section: Receptor-and Matrix-associated Cellescaffold Interactions Anmentioning
confidence: 98%
“…The positive effects of high-molecular-weight HA may be mediated by creating a favorable environment for regeneration by reducing degradative enzymes, rather than by having a direct stimulatory effect on cartilage matrix synthesis. Lack of a similar effect on expanded chondrocytes may be explained by the altered expression of CD44 by expansion [49]. It may also be possible that the high amount of sulfated GAGs measured by the dimethylmethylene blue assay, which is generally thought to represent aggrecan production by chondrocytes, may at least partly be explained by the production of other proteoglycans.…”
Section: Polyactive™mentioning
confidence: 92%